Pembentukan Public Sphere dalam Game Online - Fadhly Hafizh; Firmansyah; Dadi Ahmadi (Bandung Conference Series: Journalism, 2023)
Abstract. Public space is a medium for humans to be able to gather, have recreation, and also open a discussion room. Public space can occur in real life (real space) and in cyberspace (virtual space), this is because public space can be created anywhere, even in the world of online games, public space can be created by the players. One of the online games that has the potential to form a public space is the GTA V Online game, this can happen because in the GTA V Online game the players are connected to an internet network from all over the world and are also assisted by an additional feature, namely the voice chat feature. The purpose of this study is to determine the formation of the public sphere in the game GTA V Online, this study uses a qualitative research method with a case study approach, this research is then assisted by the public sphere theory of Jurgen Habermas. Habermas raises what he calls "institutional criteria", a character that conveys what Habermas meant by the theory of public space, the criteria are divided into three namely, disregard of status, domain of common concern, and inclusivity. The results of this study are the formation of public space in the online game GTA V which is carried out by the players. The results of this study include what Habermas calls institutional criteria, namely, disregard of status, domain of common concern, and inclusivity. Abstrak. Ruang publik (public space) menjadi media bagi manusia untuk bisa berkumpul, berekreasi, dan juga membuka ruang diskusi. Ruang publik dapat terjadi di kehidupan nyata (real space) dan di dunia maya (virtual space), hal ini karena ruang publik dapat diciptakan dimana saja, hingga dalam dunia game online pun ruang publik dapat diciptakan oleh para pemainnya. Salah satu game online yang memiliki potensi dalam pembentukan ruang publik yaitu game GTA V Online, hal ini bisa terjadi karena dalam game GTA V Online para pemain terhubung dalam satu jaringan internet dari seluruh dunia dan juga dibantu oleh fitur tambahan yakni fitur voice chat. Tujuan dari penelitian ini yaitu mengetahui pembentukan public sphere dalam game GTA V Online, penelitian ini menggunakan metode penelitian kualitatif dengan pendekeatan studi kasus, penelitian ini lalu dibantu dengan teori public sphere Jurgen Habermas. Habermas memunculkan apa yang disebutnya sebagai “institutional criteria”, sebuah karakter yang mengantarkan apa yang dimaksud Habermas dengan teori ruang publik tersebut, kriteria tersebut dibagi menjadi tiga yakni, disregard of status, domain of common concern, dan inclusivity. Hasil penelitian ini yakni adanya pembentukan ruang publik dalam game online GTA V yang dilakukan oleh para pemainnya, hasil penelitian pada penelitian ini meliputi apa yang disebut oleh Habermas sebagai institutional criteria yakni, disregard of status, domain of common concern, dan inclusivity.